Factorise 3𝑝𝑞4 − 12𝑞2𝑝6 fully.

3pq4 - 12q2p6 = 3(pq4-4q2p6) = 3p(q4-4q2p5) = 3pq2(q2-4p5)

Answered by Ellica M. Maths tutor

1817 Views

See similar Maths 13 Plus tutors

Related Maths 13 Plus answers

All answers ▸

Solve this equation: 3x-10=12x-7


solve the following equation: x^2 - 7x -15 = 3


Work out the value of: 2+8x3


4, 7, 9, 10, 10 mean, median, mode, range


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences